(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The Kandovan region in Iran is physically and geologically similar to the Cappadocian region in Turkey where fibrous zeolites, including erionite, have been found in volcanic tuffs. In some Cappodocian villages there is strong evidence that erionite, and possibly related minerals, are responsible for the high level of mesothelioma found there. So, although mesothelioma clusters have not been reported in Kandovan, it is a plausible hypothesis that many cases of mesothelioma in Iran may be due to naturally occurring fibrous zeolites. Methods: A detailed study of Iranian geology was made to determine similarities between the Kandovan region and Cappadocia, ‘inter-mountain zones’ in the Western US and Mexico. Areas where mesothelioma cases probably attributable to erionite exposure have been found. Results: Although there is a long history of asbestos use in Iran many cases of mesothelioma do not present with positive asbestos exposure histories. Since fibrous zeolites are so widespread, why have not more mesotheliomas attributable to them been found throughout Iran? Various possible reasons were explored including misdiagnosis, poor surveillance, a general lack of awareness that this tumor may be linked to mineral fibre exposure. There is also the analytical problem of identifying fibrous erionite in lung tissue. Conclusions: There is every reason to believe mesotheliomas due to fibrous zeolite including erionite will be found in Iran. The most likely places to find them are the villages that look very similar to those found in Cappadocia since these are based upon similar geological formations.